Hula as a physical activity and social support intervention for sustained activity in female breast and gynecologic cancer survivors - Bantum, Erin O.; Yamada, Paulette M.; Makolo, TeMoana; Yu, Herbert; Pagano, Ian; Subia, Natalie; Walsh, Catherine; Loo, Lenora W. M. (Frontiers in Psychology, 2023)
Background: Physical activity decreases improves health and psychosocial functioning for people who have been diagnosed with cancer. Native Hawaiians face disparities for some cancers, including breast cancer. Delivering culturally grounded interventions has the potential to improve enjoyment and adherence to the intervention. We sought to test the adherence and impact of a 6 month randomized wait-list controlled trial of hula. Methods: In this randomized wait-list controlled design people who had been diagnosed with breast or gynecologic cancers were invited to participate with other cancer survivors in a group based setting. Participants were randomized to begin hula immediately or after six months. Attendance was collected and heart-rate measured three times per session. In addition, demographic data, self-report psychosocial data, and biological data (findings will be reported elsewhere) were collected at three time points: baseline, 6 months, and 12 months. The study included six months of hula, twice per week, 60 minutes each session. In addition, participants committed to practice 60 minutes per week at home. Results: Participants in the study (n = 42) attended, on average, 72% of the sessions. Significant increase in moderate physical activity (d=0.50, p=0.03) was observed in the intervention versus control group. For the measures of intraindividual changes pre-and post-intervention, an increase in total physical activity were seen in the